Sniffing Out Paediatric Gastrointestinal Diseases: The Potential of Volatile Organic Compounds as Biomarkers for Disease. Issue 6 (December 2016) - Buijck, Martin; Berkhout, Daniel J.C.; de Groot, Evelien F.J.; Benninga, Marc A.; van der Schee, Marc P.C.; Kneepkens, Corneille Marie Frank; de Boer, Nanne K.H.; de Meij, Tim G.J.
Abstract : ABSTRACT: The diagnostic work-up and follow-up of paediatric functional gastrointestinal disorders and organic conditions usually includes invasive tests, carrying a high burden on patients. There is a place, therefore, for novel, noninvasive disease-specific biomarkers. Volatile organic compounds (VOCs), originating from (patho)physiological metabolic processes in the human body, are excreted as waste products through all conceivable bodily excrements. The spectrum of VOCs harbours a magnificent source of information, with the potential to serve as noninvasive diagnostic biomarkers and to monitor disease activity. VOC analysis has been studied in children and infants with a variety of gastrointestinal diseases, including inflammatory bowel disease, liver diseases, irritable bowel syndrome, necrotizing enterocolitis and infectious diarrhoea. Most of these studies, although limited in sample size, show that patients can be discriminated from controls based on their VOC profiles, underscoring the potential of VOC analysis in diagnosis and follow-up. Currently, however, the application of VOC analysis in clinical practice is limited; substantial challenges, including methodological, biological, and analytical problems, still need to be met. In this review we provide an overview of the available literature on the potential of VOCs as biomarkers for paediatric gastrointestinal diseases. We discuss the available techniques to analyse VOCs and provide topics for VOC-related research, which need to be addressed before VOC diagnostics can be implemented in daily clinical practice.